Clinical analysis of a case of neonatal exfoliative esophagitis in an 18-day-old neonate - Zu-Qin Yang; Jing-Yun Mai; Min-Li Zhu; Xiu-Man Xiao; Xiao-Xiao He; Shang-Qin Chen; Zhen-Lang Lin (BMC, 2019)
Abstract Background This study aims to provide guidance for clinical work through analysis of the clinical characteristics, endoscopic and pathological manifestations, diagnosis, and treatment of an 18-day-old neonate with exfoliative esophagitis. Case presentation The patient presented with vomiting but the parents did not pay too much attention. The pathological report revealed numerous fibrinous exudative necrotic, and inflammatory cells, as well as a small amount of squamous epithelium. Furthermore, milk allergy factors were considered. Conservative treatments, such as fasting, acid suppression, mucosal protection, parenteral nutrition, and the replacement of anti-allergic milk powder were given. Thereafter, endoscopic examination revealed that the patient returned to normal, and was discharged after 21 days. Conclusions Exfoliative esophagitis has multiple causes; and has characteristic clinical and endoscopic manifestations. Endoscopic examination after 18 days presentation and conservative therapy revealed that the esophagus had returned to a normal appearance and the patient was discharged. Following discharge, the parents were advised to feed the patient ALFERE powder. Attention should be given to the timely detection of complications and corresponding treatment.